Intervensi Promosi Kesehatan Pada Ibu Hamil Dan Ibu Balita Dalam Pencegahan Stunting - Cut Khairunnisa; Cut Sidrah Nadira; Muhammad Rizky Simanjuntak; Oriza Rifki Ramadhan (Publikasi Indonesia, 2022)
Stunting is a big problem in Aceh Province, especially North Aceh. Where North Aceh became one of the districts that became the locus of stunting. From 40,762 children under five in 2021 in North Aceh, the number of stunting reached 5,845 people. This figure reaches 45 percent of the total toddlers. West Reuleut is one of the villages in Muara Batu District which has a fluctuating stunting rate from year to year. Generally the incidence of stunting occurs due to poor parenting, mother's knowledge about how to do proper parenting is still very limited. The mechanism for implementing this service is by providing health promotion interventions to pregnant women and mothers with toddlers regarding the prevention of stunting since the first 1000 days of life. The implementation of the educational intervention was carried out by counseling using audio-visual media to pregnant women and mothers of toddlers as well as the practice of compiling menus for toddlers, pregnant women and breastfeeding mothers as well as monitoring and evaluation to establish relationships and find out the development of partnerships in implementing stunting prevention in the village of West Reuleut. After the end of this service activity, it was concluded that there was an increase in knowledge of pregnant women and mothers of children under five about stunting prevention efforts since the first 1000 days of life. Based on statistical tests, it shows that the health promotion interventions provided have an influence in increasing the knowledge of pregnant women and mothers of children under five. This increase in knowledge is expected to reduce the incidence of stunting, especially in the village of West Reuleut.